Chemogenomic analysis reveals key role for lysine acetylation in regulating Arc stability. Issue 1 (December 2017) - Lalonde, Jasmin; Reis, Surya; Sivakumaran, Sudhir; Holland, Carl; Wesseling, Hendrik; Sauld, John; Alural, Begum; Zhao, Wen-Ning; Steen, Judith; Haggarty, Stephen
Abstract The role of Arc in synaptic plasticity and memory consolidation has been investigated for many years with recent evidence that defects in the expression or activity of this immediate-early gene may also contribute to the pathophysiology of brain disorders including schizophrenia and fragile X syndrome. These results bring forward the concept that reversing Arc abnormalities could provide an avenue to improve cognitive or neurological impairments in different disease contexts, but how to achieve this therapeutic objective has remained elusive. Here, we present results from a chemogenomic screen that probed a mechanistically diverse library of small molecules for modulators of BDNF-induced Arc expression in primary cortical neurons. This effort identified compounds with a range of influences on Arc, including promoting its acetylation—a previously uncharacterized post-translational modification of this protein. Together, our data provide insights into the control of Arc that could be targeted to harness neuroplasticity for clinical applications. The activity-regulated cytoskeleton-associated protein (Arc) has been implicated in synaptic plasticity and memory consolidation. Here the authors show that Arc acetylation regulates its stability and identify small molecules that modulate Arc expression.